HUBUNGAN ANTARA INDEKS PRESTASI DENGAN KEMAMPUAN PENYELESAIAN MASALAH PADA TOWER OF HANOI SUATU MODEL PENILAIAN FUNGSI EKSEKUTIF DAN PEMBELAJARAN - Yuda Turana* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION TOWER OF HANOI TOH IS A POPULAR TOOL COMMONLY USED FOR EXECUTIVE FUNCTION EVALUATION UNLIKE THE STANDARD COGNITIVE TESTS ASSESSMENT USING TOH CAN BE REPEATED AND THE LEVEL OF COMPLEXITY CAN BE ADJUSTED HENCE TOH CAN BE USED TO EVALUATE THE LEVEL OF LEARNING COGNITIVE FUNCTION